The construction of a green and efficient system for the separation of polyprenols from Ginkgo biloba leaves. (January 2021) - Zhang, Chang-Wei; Li, Ming-Fei; Qi, Zhi-Wen; Tao, Ran; Ye, Jian-Zhong; Xue, Xing-Ying; Wang, Cheng-Zhang
Graphical abstract: Highlights: Ball milling was the best cell disruption assisted extraction mode for polyprenyl acetates. The amount of polyprenyl acetates extracted by DES could reach 89.88 mg/g. Ball milling coupled DES was green and efficient extraction method for polyprenyl acetates. The purity of polyprenyl acetates separated by synthesized material could reach 71.28 %. Molecular distillation was suitable for industrial production of polyprenols with high purity. Abstract: The aim of this work was to construct a new type of system for the green extraction and efficient separation of Ginkgo biloba leaf polyprenols (GBP). First, cell disruption technologies (enzymolysis, ultrasound, microwave and ball milling) coupled with deep eutectic solvents (DES) were used to extract polyprenyl acetates (PA) from Ginkgo biloba leaves. Results showed that ball milling was the best assisted extraction method, and the amount of PA was 89.88 mg/g. Then, a novel silver-loaded material with selectivity for PA was synthesized, characterized and utilized to absorb PA from the DES extraction solution. The purity of the PA quickly reached 71.28 % after being separated by the silver-loaded material. Finally, saponification and molecular distillation were adopted to remove non-GBP ingredients, and a high-purity GBP (99.80 %) was obtained by optimizing its processing conditions. This study provides a technical support for the development of a green and efficient GBP separation method and lays the foundation for the fabrication of GBP-based drugs, health products and cosmetics.